Penerapan Model Pembelajaran Kooperatif Times Games Tournament untuk Meningkatkan Keaktifan Belajar Siswa pada Pembelajaran Pendidikan Agama Islam - Alfina Alawiyah; Jijim Sukron; Muhammad Aditya Firdaus (Prodi PAI STAI Sumatera Medan, 2023)
One of the mistakes in activating student learning is due to an error in choosing a learning model. The purpose of this research is to see the average difference in increasing student learning activity through the use of cooperative learning models of the type of Teams Games Tournament. This study uses quasy experiment researchers. Techniques or data collection carried out in this study were pre- test and post- test, in taking the sample using purposive sampling. The data analysis technique used in this study was the normality test using the Shapirowilk test, the hypothesis testing using the Mann- Whitney test and the n- gain test. The results in this study indicate that the use of the Teams Games Tournament (TGT) model can significantly increase student learning activity, this is evident from the results of the n- gain test which obtained a mean value of 0.8913 or 0.90 for the experimental class, while the control class obtained a mean value 0.4921 or rounded to 0.50 which is smaller than the experimental class so that based on the interpretation of the effectiveness of the n- gain value if it is greater than the value of 0.76 it can be concluded that the use of cooperative learning models of the type of Teams Games Tournament can increase student learning activity.